Wacana Komunikasi Politik Bagi Politisi Dalam Mempertahankan Eksistensinya Melalui Perspektif Forensik Komunikasi - Fidya Faza Faraid; Ibnu Hamad; Yunita Sari (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
This research aims to analyze the political communication discourse of the politician "Fahri Hamzah" in maintaining his existence. The paradigm used in this research is the constructivist paradigm. Using a qualitative approach, Teun Van Dijk's communication forensic discourse analysis method. The subject of this research is Fahri Hamzah as deputy general chairman of the Gelora party. The object of his research is his political statements. The data used in this research uses two types of data sources, namely primary and secondary data sources. Data collection techniques are carried out by observation, interviews, questionnaires, documentation and a combination of the four. Meanwhile, data analysis techniques use data reduction, data display and data conclusion. The data validity technique uses source triangulation. Meanwhile, the theories used in this research are discourse analysis theory, forensic communication theory and social construction theory. Based on the research results, a conclusion was obtained about Fahri Hamzah's political discourse which is Philosophische Grondslag as a reference for politics. The characteristics of political communication are carried out up and down as well as vertically and horizontally. Fahri Hamzah manages politics with minimal motives of science-based pragmatism. In the future, with a consistent political tone, Fahri Hamzah can maintain his existence thereby providing many very good and positive political lessons for the people